The Effect of Visual Feedback on Writing Size in Parkinson’s Disease - Adriaan R. E. Potgieser; Elizabeth Roosma; Martijn Beudel; Bauke M. de Jong (Parkinson's Disease)
Parkinson’s disease (PD) leads to impairment in multiple cognitive domains. Micrographia is a relatively early PD sign of visuomotor dysfunction, characterized by a global reduction in writing size and a decrement in size during writing. Here we aimed to investigate the effect of withdrawal of visual feedback on writing size in patients with PD. Twenty-five patients with non-tremor-dominant PD without cognitive dysfunction and twenty-five age-matched controls had to write a standard sentence with and without visual feedback. We assessed the effect of withdrawal of visual feedback by measuring vertical word size (i), horizontal length of the sentence (ii), and the summed horizontal word length without interspacing (iii), comparing patients with controls. In both patients and controls, writing was significantly larger without visual feedback. This enlargement did not significantly differ between the groups. Smaller handwriting significantly correlated with increased disease severity. Contrary to previous observations that withdrawal of visual feedback caused increased writing size in specifically PD, we did not find differences between patients and controls. Both groups wrote larger without visual feedback, which adds insight in general neuronal mechanisms underlying the balance between feed-forward and feedback in visuomotor control, mechanisms that also hold for grasping movements.